2012
DOI: 10.1603/me12066
|View full text |Cite
|
Sign up to set email alerts
|

Biocompatibility of Antimicrobials to Maggot Debridement Therapy: Medical MaggotsLucilia sericata(Diptera: Calliphoridae) Exhibit Tolerance to Clinical Maximum Doses of Antimicrobials

Abstract: The larvae of calliphorid ßies are used to debride wounds of patients with severe tissue destruction, often concurrently with antimicrobials. The current study evaluates the effects of ceftazidime, tobramycin, amikacin, gentamicin, polymyxin B, doxycycline, paromomycin, amphotericin B, sodium stibogluconate, and miltefosine at 1, 10, and 100ϫ the Maximum Clinical Concentration (mg/kg/d) in raw liver assays. Effects on larvae were small and depended on dose and antimicrobial formulation, with hours in assay (24… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…The survivability of the L. sericata maggots was significantly deteriorated by the antibiotics, whereas antibiotics improved the breeding conditions for C. vomitoria . According to Peck and Kirkup, the maggot survival of L. sericata remains unaltered by therapeutic doses of the antibiotics ceftazidime, tobramycin, amikacin, gentamicin, polymyxin B, doxycycline and paromomycin (Peck & Kirkup, 2012). A comparison of the survivability of the control groups shows that in our study the survivability of the control had a value of 98,9%, whereas the survivability in the study of Peck and Kirkup was between 88,9% and 94,6%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The survivability of the L. sericata maggots was significantly deteriorated by the antibiotics, whereas antibiotics improved the breeding conditions for C. vomitoria . According to Peck and Kirkup, the maggot survival of L. sericata remains unaltered by therapeutic doses of the antibiotics ceftazidime, tobramycin, amikacin, gentamicin, polymyxin B, doxycycline and paromomycin (Peck & Kirkup, 2012). A comparison of the survivability of the control groups shows that in our study the survivability of the control had a value of 98,9%, whereas the survivability in the study of Peck and Kirkup was between 88,9% and 94,6%.…”
Section: Discussionmentioning
confidence: 99%
“…A comparable study on the influence of levofloxacin and ceftriaxone The survivability of the L. sericata maggots was significantly deteriorated by the antibiotics, whereas antibiotics improved the breeding conditions for C. vomitoria. According to Peck and Kirkup, the maggot survival of L. sericata remains unaltered by therapeutic doses of the antibiotics ceftazidime, tobramycin, amikacin, gentamicin, polymyxin B, doxycycline and paromomycin (Peck & Kirkup, 2012).…”
Section: Pupationmentioning
confidence: 99%
“…Producing a new cell line from C. vicina will thus support basic and applied research including the characterisation of novel antimicrobial substances (antimicrobial peptides), and other C. vicina molecules involved in tissue regeneration and/or recovery. This will enable a better understanding of the mechanisms underlying the use of larval therapy in patients with chronic wounds, as reported for other species from the Calliphoridae family ( Limsopatham et al., 2017 ; Peck and Kirkup 2012 ). This study's main objective was thus to establish and characterise, for the first time, a new C. vicina embryonic tissue-derived cell line.…”
Section: Introductionmentioning
confidence: 92%
“…These researchers found that antimicrobials can be used in combination with MDT without diminishing the therapeutic activity of the medicinal maggots. Most relevant to the application of MDT in Disaster Medicine is the latest research emerging from the WRAIR where Peck and colleagues tested the resilience of medicinal maggots during transport in US military aircraft 22 . The authors have shown that medicinal maggots can withstand conditions that exist during military evacuation and transfer flights and could, therefore, be used in the treatment of wounds during the evacuation process.…”
Section: Introductionmentioning
confidence: 99%
“…20 In parallel, Peck and Kirkup investigated the effect of antimicrobials, including antibiotics and antifungals, on medicinal maggots. 21 These researchers found that antimicrobials can be used in combination with MDT without diminishing the therapeutic activity of the medicinal maggots. Most relevant to the application of MDT in Disaster Medicine is the latest research emerging from the WRAIR where Peck and colleagues tested the resilience of medicinal maggots during transport in US military aircraft.…”
Section: Introductionmentioning
confidence: 99%